Development of E-Learning Module in PjBL to Improve Students' Learning Independence and Creativity on the Material of Biodiversity - Nanik Yuniastuti; Paidi Paidi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research aims to develop an appropriate e-learning module to support the Project-Based Learning (PjBL) model, determine the practicality of the PjBL e-learning module, and assess the effectiveness of the PjBL e-learning module in enhancing phase E students' learning independence and creativity on biodiversity material. The type of research conducted is research and development (R&D) using the ADDIE model. The research findings indicate that, based on assessments by material experts, media experts, and education experts who also act as linguists, the developed e-learning module is considered feasible for use. This assessment implies that the e-learning module contains valid biological content, adheres to pedagogical principles, and uses appropriate language. The findings also indicate that, based on practitioners' opinions and observations of learning implementation, the e-learning module is practical for use in teaching.The results of the descriptive analysis obtained an N-gain score of 0.6 on the learning independence variable, which indicates an increase in the moderate criteria, while the N-gain score on the creativity variable of 0.7 also indicates an increase in the moderate criteria. The results of the Wilcoxon Signed-Rank Test on learning independence and creativity showed a p-value ≤ 0.05 and H1 was accepted, which means there is a significant difference in learning independence and student creativity by using e-learning module. It can be concluded that the developed e-learning module is effective in improving learning independence and student creativity at SMAN 2 Yogyakarta, as evidenced by statistical data analysis.